PENGARUH PELAPISAN SERAT KARBON PADA ALUMUNKUM 6061 TERHADAP SIFAT MEKANIK - Muhammad Rafli; Priyagung Hartono; Mochammad Basjir (Universitas Islam Malang, 2024)
ABSTRACT Knowledge about technology will continue to develop by itself through individual thoughts, the rapid progress of science and technology opens up thoughts and ideas in forming materials and even modifying them, which in general the frame or chassis of vehicles uses steel, steel is very heavy compared to aluminum. but changing a material will cause a lack of safety and comfort because aluminum is known to have a very low level of strength when compared to heavy metals. So carbon fiber was added to the surface of aluminum 6061 with carbon fiber thicknesses of 4 mm, 8 mm and 10 mm, in fiber directions of 45o and 90o by carrying out impact testing and bending testing to see the strength of the material when loaded. T The presence of 45o and 90o fiber directions slightly affects the maximum load on 6061 aluminum with a woven carbon fiber layer, where the average value in the 45o direction is 90.7 and 90o 80.8. However, by reducing the thickness of aluminum 6061, it reduces the bending strength value of the specimen due to the lack of moment of inertia, the coating specimen also appears to be coming off due to the lack of adhesion of the carbon fiber webbing to aluminum 6061. The attachment process is influenced by the hardness of the specimen so that the rougher the material structure, the higher the coefficient. high friction, Keywords: Aluminum 6061; Carbon Fiber; Impact Test; Bending Test.